China in the South China Sea Dispute: Between Status Quo and Revisionist - Albert Triwibowo (Parahyangan Center for International Studies, 2014)
Abstract: The paper is trying to look whether China is a status quo power or a revisionist power in theSouth China Sea dispute based on status quo indicator developed by Johnston and perspectives onconformity towards norms. Meanwhile, this paper argues that China is neither a status quo nor arevisionist in the South China Sea dispute to the extent of its compliance with the Declaration on theConduct of Parties (DoC) in the South China Sea. Using status quo indicators developed by Johnstonand also the perspectives on conformity and violation towards norm, it is found that China's position inthe South China Sea is determined by its interests over the disputed area. A moral dilemma betweenexpected behaviors in the South China Sea based on China's involvement in the DoC and China's otherself interests. Moreover, China has been conducting activities which fall under both categories, bothstatus quo and revisionist. China is lying in the middle between status quo and revisionist in the SouthChina Sea dispute, between an obligatory action that is mandated by the DoC and the desire to act inorder to pursue its self-interest such as its sovereignty claim, natural resources, and geostrategicposition of the disputed territory. China's position in the South China Sea dispute as well as its moraldilemma in the end could be seen through its mixed and constrained actions indicated by an aggressiveact and a justification related to the aggressive act.Key words: China, South China Sea Dispute, Status Quo, Revisionist, Norm, DoC.